2020
DOI: 10.3390/plants9111622
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges in Studies of Host-Pathogen Interactions and Management of Verticillium dahliae in Tomatoes

Abstract: Tomatoes (Solanum lycopersicum L.) are a valuable horticultural crop that are grown and consumed worldwide. Optimal production is hindered by several factors, among which Verticillium dahliae, the cause of Verticillium wilt, is considered a major biological constraint in temperate production regions. V. dahliae is difficult to mitigate because it is a vascular pathogen, has a broad host range and worldwide distribution, and can persist in soil for years. Understanding pathogen virulence and genetic diversity, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 270 publications
(427 reference statements)
0
26
0
Order By: Relevance
“…It was reported that the V. dahliae infected tomato plants had a 91.25% disease severity index after 12 weeks (Ait-Rahou et al, 2020). This vascular pathogen with a wide host range was distributed worldwide and could be able to survive in the soil for several years (Acharya et al, 2020). In this study, the most effective treatment against V. dahliae was Cr40, with 25.33% disease severity index and 66.67% suppression rate.…”
Section: Effect Of C Rosea On Disease Severity Indexmentioning
confidence: 82%
“…It was reported that the V. dahliae infected tomato plants had a 91.25% disease severity index after 12 weeks (Ait-Rahou et al, 2020). This vascular pathogen with a wide host range was distributed worldwide and could be able to survive in the soil for several years (Acharya et al, 2020). In this study, the most effective treatment against V. dahliae was Cr40, with 25.33% disease severity index and 66.67% suppression rate.…”
Section: Effect Of C Rosea On Disease Severity Indexmentioning
confidence: 82%
“…In the field, it coevolves with host plant to appear a strong pathotype (Atallah et al 2010;Song et al 2020). Many researches have been made to control Verticillium wilt, such as breeding resistant cultivars, crop rotation, developing soil fumigants, applying chemical fungicides, as well as biological control (Acharya et al 2020;Ingram et al 2020;Zhang et al 2021). Unfortunately, Verticillium wilt still results in extensive economic losses.…”
Section: Introductionmentioning
confidence: 99%
“…V. dahliae infects over 200 dicotyledon plant species such as cotton, tobacco, tomatoes, Arabidopsis ( Song et al, 2020 ). Among tomato diseases, Verticillium wilt is a major biotic stressor of tomato production ( Acharya et al, 2020 ). In cotton, the average yield loss caused by Verticillium wilt is approximately 10–35% annually; therefore it is urgent to understand the interaction mechanism between plants, especially crops, and V. dahliae .…”
Section: Introductionmentioning
confidence: 99%